Deconstruction of Communication Structures in the Digital Age: Public Hysteria and Government Panopticon - Rohimah, Afifatur; Bustomi, Abu Amar; Zuhriyah, Luluk Fikri; Jupriono, D. (Universitas Negeri Surabaya, 2024)
The digital age and the pandemic have significantly impacted communication. The vast amount of data shared by internet users in virtual spaces has made issues related to the pandemic popular. Research was conducted in Indonesia to uncover the hidden meaning behind the pandemic's metanarrative. The study aimed to identify the government's interests behind the pandemic, dismantle them, and digitize communication. The research used Jacques Derrida's